Acute kidney injury after thoracic surgery: a proposal for a multicentre evaluation (MERITS). (8th August 2019) - Naruka, Vinci; Mckie, Mikel A; Khushiwal, Rasoel; Clayton, James; Aresu, Giuseppe; Peryt, Adam; Villar, Sofía S; MacKay, Jon; Coonar, Aman S
Abstract: OBJECTIVES: Because the mortality rate is very low in thoracic surgery, its use as a quality discriminator is limited. Acute kidney injury (AKI) is a candidate measure because it is associated with increased rates of morbidity and mortality and is partly preventable. The incidence of AKI after thoracic surgery is not well documented. We conducted an audit to determine the incidence and outcomes of AKI. This audit became a pilot project, and the results indicate the feasibility of a larger study. METHODS: Retrospective data on renal function post-thoracic surgery were collected at a tertiary cardiothoracic unit over 12 months. Renal impairment was classified according to the Kidney Disease Improving Global Outcomes criteria. RESULTS: Of 568 patients (mean = 59  ±  SD 18; 38% women), AKI was diagnosed in 86 (15.1%) within 72 h post-thoracic surgery based on the Kidney Disease Improving Global Outcomes staging system (stage 1, n  =   55; stage 2, n  =   25; stage 3, n  =   6). Significant differences were found in postoperative length of stay (3 vs 5 days; P  <   0.001) of patients with and without AKI. There was a significant difference between the age groups of patients with and without AKI ( P  <   0.05) in the open surgical group but not in the group having video-assisted thoracoscopic surgery (VATS). There was no significant difference in the mortality rates between patients with and without AKI. CONCLUSIONS: The incidence of AKI after thoracic surgery was 15.1%. AKI was associated with longer hospital stays and was more likely in ≥60-year-old patients after open surgery than after VATS. Reducing AKI could improve patient outcomes. We propose that AKI may be a useful quality measure in thoracic surgery. We are developing a multicentre audit based on this approach.